ESG Integration in Sustainability Management : Driving Corporate Value in The Green Era - Adrian Eka Darma Serang; Hidayani Hidayani; Nugroho Noto Diharjo (PT. Hafasy Dwi Nawasena, 2025)
The global shift from shareholder-oriented governance toward stakeholder capitalism has positioned Environmental, Social, and Governance (ESG) integration as a strategic instrument for corporate value creation. However, empirical findings on the ESG–corporate value relationship remain inconsistent, particularly regarding the internal mechanisms linking ESG to economic performance. This study aims to examine the effect of ESG Integration on Sustainability Management and Corporate Value, as well as the mediating role of Sustainability Management. Using a quantitative explanatory approach with Structural Equation Modeling–Partial Least Squares (SEM–PLS), data were collected from 180 companies implementing ESG practices. The results reveal that ESG Integration has a positive and significant effect on Sustainability Management and Corporate Value. Furthermore, Sustainability Management significantly influences Corporate Value and mediates the relationship between ESG Integration and Corporate Value. These findings confirm that ESG functions not merely as a legitimacy tool but as a value driver when structurally embedded within sustainability management systems.